2021
DOI: 10.3390/toxins13010066
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Removal of Cyanotoxins by Al-Doped ZnO Nanoparticles with Visible-LED Irradiation

Abstract: The ZnO-based visible-LED photocatalytic degradation and mineralization of two typical cyanotoxins, microcystin-LR (MC-LR), and anatoxin-A were examined. Al-doped ZnO nanoparticle photocatalysts, in Al:Zn ratios between 0 and 5 at.%, were prepared via sol-gel method and exhaustively characterized by X-ray diffraction, transmission electron microscopy, UV-vis diffuse reflectance spectroscopy, photoluminescence spectroscopy, and nitrogen adsorption-desorption isotherms. With both cyanotoxins, increasing the Al c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Cyanotoxins are classified according to their chemical structure mainly into cyclic peptides, alkaloids, lipopeptides, non-protein amino acids and lipoglycans (Du et al 2019). Some of the cyanotoxins such as microcystin (MC), nodularin (NOD) and cylindrospermopsin (CYN) are hepatotoxins (Benamara et al 2021). Moreover, CYN is also a genotoxin (Žegura et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanotoxins are classified according to their chemical structure mainly into cyclic peptides, alkaloids, lipopeptides, non-protein amino acids and lipoglycans (Du et al 2019). Some of the cyanotoxins such as microcystin (MC), nodularin (NOD) and cylindrospermopsin (CYN) are hepatotoxins (Benamara et al 2021). Moreover, CYN is also a genotoxin (Žegura et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this broader band gap value of ZnO restricted its use as a photocatalyst under solar radiation. Several researchers, including Benamara et al ., have suggested that the application of doping or surface modification techniques to inhibit photocorrosion of ZnO during the continuous photocatalytic process may be effective [10] . An effective photocatalyst should have the right molar absorptiion and show absorption in the broader area.…”
Section: Introductionmentioning
confidence: 99%
“…Three other papers address different advanced oxidation processes used to remove cyanotoxins [7][8][9]. Advanced oxidation processes involve a set of oxidative water treatments, including treatment with UV-O 3 , UV-H 2 O 2 , the Fenton process, the photo-Fenton process, and nonthermal plasmas as well as sonolysis, photocatalysis, and radiolysis, all based on the production of powerful, highly reactive oxidants.…”
mentioning
confidence: 99%
“…Although the Fenton process is a promising advanced oxidation technique that can be easily implemented at full scale worldwide due to its simplicity and highly cost-effective technology, the water matrix effect and large-scale volumes need to be investigated to evaluate the process for application in treating cyanotoxins because the presence of scavengers and competing species identified in real water matrices may affect degradation kinetics. Next, Benamara et al [8] report that Al-doped ZnO nanoparticles are effective photocatalysts for degrading and mineralizing two typical cyanotoxins, microcystin-LR and anatoxin-A, under visible-light irradiation with light emitting diodes (LEDs). Central to that process is using easily fabricated Al-doped ZnO nanoparticles to act as photocatalysts for water decontamination.…”
mentioning
confidence: 99%
See 1 more Smart Citation